Microvascular Parameters Help to Predict Stroke Risk in the Asian Diabetic Population in Taiwan: A Population Based Case-Control Study - Lo, Sui-Foon; Chen, Wei-Liang; Muo, Chih-Hsin; Chen, Pei-Chun; Chen, Shih-Yin; Kuo, Chih Lan; Sung, Fung-Chang (Frontiers in Neurology, 2018)
Intensive glycemic control has not shown consistent findings in stroke prevention for diabetes patients, particularly for those with microvascular complications. This case-control study evaluates the risks of stroke in Asian diabetic population with microvascular complications. From the insurance claims of Taiwan, we identified 67,426 type 2 diabetic mellitus (DM) patients with newly diagnosed stroke in 2000-2011 and 134,852 randomly selected controls without stroke, matched by sex, age, and diagnosis years of DM. Conditional logistic regression analysis measured crude odds ratios (OR) and adjusted odds ratio (aOR) of stroke and 95% confidence intervals (CI) for associations with demographic status, comorbidities, and microvascular complications: retinopathy (RetP), neuropathy (NeuP) or nephropathy (NepP). The aOR of stroke increased significantly associated with each complication: 1.47 with RetP, 1.73 with NeuP and 1.23 with NepP. The risk increased further when there was a combination of complications. The overall aOR of stroke was 2.83 (95% CI 2.58–3.09) for stroke patients with 3 microvascular complications. The corresponding aOR of ischemic stroke was 2.64 (95% CI 2.39-2.91) and that of hemorrhagic stroke was 4.12 (95% CI 3.25-5.22). The number of microvascular complications positively correlated to the prevalence of comorbidity (p <0.01). This study suggests that microvascular complications are significant stroke predictors, with a greater involvement for ischemic stroke than for hemorrhagic stroke. Multiple microvascular complications interactively increase the stroke risk. Our study contributes to the identification of high-risk subjects for stroke prevention and adequate glycemic control.